A Review of Minimally and Non-invasive Glucose Monitoring Techniques, Devices and Sensors - Nooshnab, Mohammad; Naghib, Seyed M.; Rahmanifard, Rouhollah; Khakpour, Elnaz (Current Analytical Chemistry, 2024)
Glucose determination, without pain and aches, is essential for biomedical applications. Minimally invasive (MI) and non-invasive (NI) are the approaches that could address these challenges. MI approaches are based on body fluids such as saliva, urine, tears, and interstitial fluid that are exploited to determine glucose levels. NI methods utilize radiation forms to determine glucose concentration without needing body fluids. In this review, MI and NI technologies and their application in glucose measurement, along with current and future devices that use these technologies, are described and discussed. Also, the principles and requirements and operational and analytical performance will be reviewed and discussed.
Keywords: non-invasive